From Mammals to Insects: Exploring the Genetic and Neural Basis of Eating Behavior. - Mahishi, D.; Agrawal, N.; Jiang, W.; Yapici, N. (Annual Review of Genetics, 2024)
Obesity and anorexia are life-threatening diseases that are still poorly understood at the genetic and neuronal levels. Patients suffering from these conditions experience disrupted regulation of food consumption, leading to extreme weight gain or loss and, in severe situations, death from metabolic dysfunction. Despite the development of various behavioral and pharmacological interventions, current treatments often yield limited and short-lived success. To address this, a deeper understanding of the genetic and neural mechanisms underlying food perception and appetite regulation is essential for identifying new drug targets and developing more effective treatment methods. This review summarizes the progress of past research in understanding the genetic and neural mechanisms controlling food consumption and appetite regulation, focusing on two key model organisms: the fruit fly Drosophila melanogaster and the mouse Mus musculus. These studies investigate how the brain senses energy and nutrient deficiency, how sensory signals trigger appetitive behaviors, and how food intake is regulated through interconnected neural circuits in the brain.